Downsizing of Housing: Negotiating Sufficiency and Spatial Norms. (June 2018) - Sandberg, Maria
Housing is one of the major sources of the environmental impact of consumption. An aspect of housing that has rarely been considered in previous studies on sustainable housing is the size of the dwelling, even though research has shown the impact of dwelling size on the environmental impact of housing to be significant. This study analyzes socio-cultural meanings about downsizing as well as norms about dwelling size. The study analyzes naturally occurring, cultural texts (media texts and corporate communications about small-sized dwellings). The study offers a view on how the meaning of downsizing is negotiated, the (in)voluntariness of downsizing emerging as the main point to be negotiated. Additionally, the study offers understanding for how norms about dwelling size are negotiated in order to normalize smaller dwellings. In these ways, the study offers researchers insights about how downsizing can be advanced in order to reduce the environmental impact of housing.